Pete the Kitty and the case of the hiccups - Dean, James 1957- (Harper, an imprint of HarperCollinsPublishers, 2019)
"Pete gets a case of the hiccups, and he doesn't know what to do! He decides to ask his wisest friends for help, like Grumpy Toad, Callie, and Bob. But Pete is still stuck with the hiccups! Will Pete the Kitty ever get rid of his terrible hiccups?''--Publisher's description
Keywords: Pete / the Cat (Fictitious character) / Juvenile fiction; Cats / Juvenile fiction; Hiccups / Juvenile fiction; Friendship / Juvenile fiction; Pete / the Cat (Fictitious character) / Fiction; Cats / Fiction; Hiccups / Fiction; JUVENILE FICTION / Animals / Cats; JUVENILE FICTION / Health & Daily Living / Diseases, Illnesses & Injuries; JUVENILE FICTION / Reader / Beginner; Pete / the Cat (Fictitious character); Friendship; Cats; Hiccups; Easy reading materials; Readers (Elementary); Humorous fiction; Children's stories; Readers (Primary); Fiction; Juvenile works; Bilderbuch; Kinderbuch